1981
DOI: 10.1111/j.1752-1688.1981.tb01238.x
|View full text |Cite
|
Sign up to set email alerts
|

WATER QUALITY FROM TWO SMALL FORESTED WATERSHEDS IN SOUTHERN ILLINOIS1

Abstract: Two intermittent streams on oak‐hickory watersheds in southern Illinois were gaged with a V‐notched weir and sampled with an automatic water sampler. For three years data were collected on flow volume and water quality. Flow volumes show large variations between years and watersheds. Samples were analyzed for Na+, K+, Ca++, Mg++, P, and NO‐3. Water quality was consistently high, although there were significant differences between watersheds. A baseline for water quality has been established for comparison afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…During the calibration period, January 1977 through October 1979, the annual flow volume was extremely variable, with the watersheds behaving quite differently (Brozka, et a l , 1981), due partly to problems experiences with the weirs. Figure 1 and Table 3 illustrate this variability.…”
Section: Stream Hydrologvmentioning
confidence: 99%
See 2 more Smart Citations
“…During the calibration period, January 1977 through October 1979, the annual flow volume was extremely variable, with the watersheds behaving quite differently (Brozka, et a l , 1981), due partly to problems experiences with the weirs. Figure 1 and Table 3 illustrate this variability.…”
Section: Stream Hydrologvmentioning
confidence: 99%
“…Annual nutrient budgets were completed for the calibration period and reported by Brozka, et al (1981). In each year there was a large net gain of K and 0rtho-P. Ca showed a net gain in all but one year and Mg showed a net loss in most years.…”
Section: Annual Nutnenr Budgetsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1985), have shown that nitrate tends to be conserved through biologic recycling within a watershed such that concentrations and loadings in streamfiow tend to be very low. Several researchers have observed a growing season minima and dormant season maxima for oxidized nitrogen in streamfiow (Hem, 1970;Likens, et a!., 1977;Brozka, et a!., 1981). In addition, Vitousek and Melillo (1979) suggest that the amount of oxidized nitrogen in streamfiow is related to the permeability of the watershed soils and the amount of soil water in the root zone.…”
Section: Introductionmentioning
confidence: 98%